Multifunctional graphene nanofiller in flame retarded polybutadiene/chloroprene/carbon black composites - Battig Alexander (De Gruyter, 2021)
To curtail flammability risks and improve material properties, flame retardants (FRs) and fillers are mixed into rubbers. High loadings of aluminum trihydroxide (ATH) and carbon black (CB) are the most used FRs and reinforcing additive, respectively, in rubbers. To reduce loading without losing mechanical properties, partial substitution of ATH as well as CB by low amounts of multilayer graphene (MLG) nanoparticles is investigated. The high aspect ratio MLG is made of ten graphene sheets. In polybutadiene/chloroprene (BR/CR) nanocomposites 3 phr MLG replaced 15 phr CB and/or 3 phr ATH. Material and mechanical properties as well as fire behavior of the nanocomposites are compared to BR/CR with 20 phr CB both with and without 50 phr ATH. MLG appears as a promising nanofiller to improve the functional properties: replacement of CB improved rheological, curing, and mechanical properties; substitution of ATH improved nanocomposite properties without affecting flame retardancy.